Antioxidant capacity, oxidative stability of mango (Mangifera indica L) seed oil in 2 varieties and two degrees of maturity - Aguirre Vargas, Elza Berta (2021)
The present work search the influence of the Edward and Kent mango varieties, in degrees of maturity partially ripe and ripe respectively, on the antioxidant capacity and oxidative stability of mango seed oil (Mangifera indica L.), previously extracted by pressing in cold, clarified by centrifugation, and stored in refrigeration under nitrogen atmosphere. The antioxidant capacity is determine by DPPH method, the oxidative stability by the Rancimat test with temperature parameters 130, 140 and 150 °C, and airflow 15 L/h. The results are evaluate by ANOVA (p˂0, 05) finding in the antioxidant capacity and other analyzes made a significant difference with a level of 95% confidence in the variables of variety and degree of maturity. Regarding the influence, the relationship will be determined that in a mature degree of maturity has a higher content of unsaturated fatty acids (oleic), and a lower content of total polyphenols, antioxidant capacity and oxidative stability. Being the oil of the variety Edward in degree of maturity ripe the most stable due to low value of the peroxide index (0,898 meq O2 / kg), acidity (1,1856%), and the higher content of total polyphenols (8,5931 mg GAE /100g) and antioxidant capacity (263,858 umoltrolox /100g), with a lifetime of 12,89 years.